Childhood cancer epidemiology in the sub-Saharan French speaking African population - (:unkn) unknown (My University, 2024)
Childhood cancer is one of the top ten causes of death in children globally. Cancers diagnosed in LMICs represent 80% of these cases. LMICs often lack functioning cancer registries, and existing ones fail to collect comprehensive data on paediatric cancers. Registration systems could be greatly assisted by structured Hospital based cancer registries. The Franco-African Pediatric Oncology Group (GFAOP) dedicated to alleviating the plight of children with cancer in Africa, embarked on a pivotal initiative in 2016 to create a centralized hospital-based childhood cancer registry within its paediatric oncology units (POU). Objectives The principal objective is to improve epidemiological information on childhood cancer in western sub-Sahara. Secondly, describe data, and evaluate quality. Another aim was analyse feasibility of implementing a standardised staging system called Toronto Paediatric Cancer Stage Guideline (TG). Finally, evaluate the possibility of developing a regional population-based cancer registry for Dakar, and identify sources of cases. Method Work was divided into three projects. Initially existing data from 13 participating units, for all registered cases from 01/01/2016 - 31/12/2018, <18, was extracted. Descriptive analysis was employed to elucidate characteristics and the heterogeneity across the POU. The notion of bandonment was described using fall out pathways. Then data from 2016 and 6 POU were dropped, and data for 2019 added. Eligible children were,15 years, residing in the country of registration, diagnosed between 01/01/2017 and 31/12/2019 with one of the 15 cancer defined by the TG. The third study focused on all cases in the Dakar region 18 diagnosed between 01/01/2017 and 31/12/2019. Initially, key public health services and geographic limits of the region covered were identified including eight services considered as potential sources. Overall survival (OS) was estimated at 3, 6 and 12 months using Kaplan-Meier metho
Keywords: African Research